Financializing Stakeholder Claims. (11th August 2015) - Crane, Andrew; Graham, Cameron; Himick, Darlene
ABSTRACT This paper examines the role of accounting in assigning financial values to stakeholder claims. Stakeholder theorists have called for metrics managers can use to coordinate stakeholder claims. We argue that accounting already serves as the dominant example of such a tool, and that its role in measuring and representing stakeholder claims, and how those representations are used by stakeholders and managers, is not well understood. We suggest that accounting financializes stakeholder claims along three inductively‐developed dimensions, namely time, security, and priority. We analyse the case of pension accounting at General Electric to theorize concerning how these dimensions shape stakeholder claims and are used by stakeholders and managers to trade‐off claims, demarcate claimants into groups, and reconstruct claims during negotiations.